Effects of marigold flower (Tagetes erecta) and turmeric rhizome (Curcuma longa) as sources of carotenoid on productive performance and carcass characteristics of dual-purpose chickens in the finishing phase - Paredes, Manuel (2022)
The aim of this study was to determine the effect of marigold flower (Tagetes erecta) and turmeric rhizome (Curcuma longa) as sources of carotenoids on the productive performance of dual-purpose chicken and carcass characteristics. In total, 120 chickens of both sexes from 84 to 112 days of age were assigned to six treatments (five repetitions per treatment and four birds per repetition), under factorial arrangement with two factors: sex (males and females) and sources of carotenoids (control, marigold and turmeric). All birds received the same concentrated feed, and the differences were the sources of carotenoids. Marigold flower and turmeric rhizome did not improve the productive performance of chickens, nor did they generate adverse effects on growth. Turmeric produced a greater reddish hue in the carcass than marigold; however, the marigold flower caused greater yellowing of the breast skin. Turmeric rhizome reduced the accumulation of abdominal fat in the carcass, with lower liver mass in relation to the bird’s body weight.